2022
DOI: 10.3389/fbioe.2022.863969
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Biomaterials for Peripheral Nerve Regeneration–Technology Trends and Translational Tribulations

Abstract: The use of autografted nerve in surgical repair of peripheral nerve injuries (PNI) is severely limited due to donor site morbidity and restricted tissue availability. As an alternative, synthetic nerve guidance channels (NGCs) are available on the market for surgical nerve repair, but they fail to promote nerve regeneration across larger critical gap nerve injuries. Therefore, such injuries remain unaddressed, result in poor healing outcomes and are a limiting factor in limb reconstruction and transplantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 136 publications
0
14
0
Order By: Relevance
“…The field of nerve regeneration is witnessing significant advancements in the design and application of implantable biomaterials. Key strategies include the integration of neurotrophic factors, chemical guidance agents, and auxiliary solute factors to foster nerve tissue repair, as well as pioneering bioartificial nerve conduits as novel therapeutic avenues ( 86 ). Moreover, the refinement of therapeutic proteins through precise dosage control, optimized release kinetics, and targeted delivery is gaining momentum.…”
Section: Graft Materialsmentioning
confidence: 99%
“…The field of nerve regeneration is witnessing significant advancements in the design and application of implantable biomaterials. Key strategies include the integration of neurotrophic factors, chemical guidance agents, and auxiliary solute factors to foster nerve tissue repair, as well as pioneering bioartificial nerve conduits as novel therapeutic avenues ( 86 ). Moreover, the refinement of therapeutic proteins through precise dosage control, optimized release kinetics, and targeted delivery is gaining momentum.…”
Section: Graft Materialsmentioning
confidence: 99%
“…NGCs generally take the shape of a hollow tube that is placed over the proximal and distal nerve injury sites, bridging the gap and providing structural support and guidance for axonal regrowth. Recently, numerous studies have demonstrated improved nerve regeneration using NGCs seeded with MSCs, nerve growth factor gradients, or biocompatible ECM to provide a supportive growth environment (Rezza et al, 2022; Wang et al, 2020). NGCs can be personalized for each patient using MRI scans to make precise copies of the nerve, such as making a bifurcated or flexible NGC (Johnson et al, 2015; Liu et al, 2022).…”
Section: Three‐dimensional Bioprintingmentioning
confidence: 99%
“…Synthetic conduits are an appealing alternative; however, they cannot successfully facilitate axonal regeneration over long distances, likely because of the lack of microstructural elements found in native nerve [38]. Newer approaches have focused on customizing nerve guide conduits, such as using 3D printing, and creating synthetic scaffolds infused with neurotrophic factors and lined with Schwann cells to create a favorable microenvironment and facilitate axonal migration along these artificial channels, which may increase the likelihood of successful nerve regeneration [39,40,41 ▪ ,42 ▪▪ ]. Simultaneous fat grafting can provide adipose-derived stem cells, which can differentiate into Schwann-like cells that guide axonal regeneration, protect against scarring and provide a favorable microenvironment with pro-regenerative properties [43].…”
Section: Managementmentioning
confidence: 99%